A study on children behavior towards learning through mobile applications (APPS) / Mazliana Mazlan - Mazlan, Mazliana (2016)
Mobile devices are ICT devices but with greater flexibility, ubiquitous connectivity and combined with the power of desktop computing. The potential impact of using mobile devices in education will result in the production of unprecedented teaching and learning technologies. There is now a real opportunity for innovative teaching and interactive learning with mobile devices with the number of mobile devices exceed the number of computers. This study is to observe on children behavior towards learning through mobile applications (apps). The observation will be done at Kinder Kaizen kindergarten with a set of observation form to evaluate the effectiveness of the mobile application and tablet on children.